2017
DOI: 10.1080/16000870.2017.1354661
|View full text |Cite
|
Sign up to set email alerts
|

Monsoon intra-seasonal variability in a high-resolution version of Met Office Global Coupled model

Abstract: Intra-seasonal oscillation (ISO) is a key ingredient of the East Asia and western North Pacific (EAWNP) summer monsoon and particularly important for seasonal forecast. This paper evaluates the seasonal means and ISOs of the EAWNP summer monsoon simulated by the latest version of the Met Office Global Coupled Model (HadGEM3-GC2) with two different atmospheric model resolutions at ~130 and ~25 km coupled to a same 0.25° × 0.25° resolution ocean model. Results show that the mean states of sea surface temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…The resulting quadrupole pattern of variability anomaly across the Indian-western Pacific sector resembles that of the seasonal mean bias (Figures 5e and 5f). These patterns are consistent with previous findings, which show that precipitation-latent heat flux feedback acts to reduce the overestimated variability in AGCMs when coupled to ocean models (e.g., Fang et al, 2017;R. Wu & Kirtman, 2005).…”
Section: The Response Of Precipitation Variability To Nudgingsupporting
confidence: 93%
See 1 more Smart Citation
“…The resulting quadrupole pattern of variability anomaly across the Indian-western Pacific sector resembles that of the seasonal mean bias (Figures 5e and 5f). These patterns are consistent with previous findings, which show that precipitation-latent heat flux feedback acts to reduce the overestimated variability in AGCMs when coupled to ocean models (e.g., Fang et al, 2017;R. Wu & Kirtman, 2005).…”
Section: The Response Of Precipitation Variability To Nudgingsupporting
confidence: 93%
“…Several studies have suggested cross-scale interactions may be fundamental in modulating the Asian monsoon annual cycle. For example, IAV of the seasonal mean monsoon rainfall is affected by the nature of ISV (e.g., Yoo et al 2010), and a realistic representation of these relationship is key for improved seasonal monsoon simulations and predictions (e.g., Achuthavarier & Krishnamurthy, 2010;Fang et al, 2017). Summertime monsoon precipitation variability is closely linked to the occurrence of severe droughts and floods, which have considerable influence on agriculture, economy, and social well-being across Asia (Udmale et al, 2014;Zheng et al, 2006).…”
Section: The Response Of Precipitation Variability To Nudgingmentioning
confidence: 99%
“…In comparing atmosphere-only to coupled GCM simulations over the summer monsoon regions, autocorrelations of day-to-day rainfall were seen to improve with coupling (Misra, 2008). Air-sea coupling was also shown to significantly improve the simulation of the BSISO (Kemball-Cook et al, 2002;Fu et al, 2003;Fu and Wang, 2004a;Klingaman et al, 2011;DeMott et al, 2014). MetUM GC2 simula-tions at resolutions of 135 and 25 km showed improved mean sea surface temperature and low-level specific humidity with finer atmospheric resolution (Fang et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…Though the intra-seasonal forecasting skills have been showing signi cant advances in recent years (Lee et al, 2015), understanding and predicting the MISOs remain one of the central tasks of the climate research community (Vitart et al, 2012;Vitart, 2014). The realistic simulation and accurate prediction of the MISOs is still challenging using the present generation of climate models due to inadequate model physics and parameterization (Fang et al, 2017;Li et al, 2018;Mishra et al, 2018).…”
Section: Introductionmentioning
confidence: 99%